Late Sandbian (Sa2) radiolarians of the Pingliang Formation from the Guanzhuang section, Gansu Province, China. (January 2022) - Perera, Siyumini; Aitchison, Jonathan C.
Abstract: A diverse, well-preserved radiolarian assemblage is reported from the Sandbian age Climacograptus bicornis Graptolite Biozone. This new assemblage, recovered from the Pingliang Formation in the Guanzhuang section, China, includes six new species along with 13 other previously described taxa. Geminusphaera new genus incorporates G . grandis n. sp. and G . kongtongensis n. sp. and is proposed for inaniguttids constructed from two distinct porous spheres bearing seven or more primary spines. Protopylentonema new genus is introduced to incorporate pylomate entactinarians with five-rayed initial spicules. It includes P . ordosensis n. sp. as well as P . aperta, P . rimata, and P . insueta that were formerly assigned to Kalimnasphaera . Micro-computed tomography investigation of skeletal microstructure supports establishment of the new genera together with other new spumellarian species: Haplotaeniatum implexa n. sp., Inanigutta quadrispinosa n. sp., and Kalimnasphaera pingliangensis n. sp. It also indicates that family-level reassignment of Etymalbaillella from the Proventocitidae to the Ceratoikiscidae is appropriate. Global distribution of Late Ordovician radiolarian occurrences highlights a strong preference for areas with equatorial to tropical sea surface temperatures. This must have led to ecological stress among radiolarian communities in adapting to global cooling in the Hirnantian. UUID: http://zoobank.org/3d3f55b8-0e70-4f9f-9738-265750d8ec3a .